Improved TEA Sensitivity and Selectivity of In2O3 Porous Nanospheres by Modification with Ag Nanoparticles - Dengke Li; Yanwei Li; Xiaohua Wang; Guang Sun; Jianliang Cao; Yan Wang (Nanomaterials, 2022)
A highly sensitive and selective detection of volatile organic compounds (VOCs) by using gas sensors based on metal oxide semiconductor (MOS) has attracted increasing interest, but still remains a challenge in gas sensitivity and selectivity. In order to improve the sensitivity and selectivity of In2O3 to triethylamine (TEA), herein, a silver (Ag)-modification strategy is proposed. Ag nanoparticles with a size around 25–30 nm were modified on pre-synthesized In2O3 PNSs via a simple room-temperature chemical reduction method by using NaBH4 as a reductant. The results of gas sensing tests indicate that after functionalization with Ag, the gas sensing performance of In2O3 PNSs for VOCs, especially for TEA, was remarkably improved. At a lower optimal working temperature (OWT) of 300 °C (bare In2O3 sensor: 320 °C), the best Ag/In2O3-2 sensor (Ag/In2O3 PNSs with an optimized Ag content of 2.90 wt%) shows a sensitivity of 116.86/ppm to 1–50 ppm TEA, about 170 times higher than that of bare In2O3 sensor (0.69/ppm). Significantly, the Ag/In2O3-2 sensor can provide a response (Ra/Rg) as high as 5697 to 50 ppm TEA, which is superior to most previous TEA sensors. Besides lower OWT and higher sensitivity, the Ag/In2O3-2 sensor also shows a remarkably improved selectivity to TEA, whose selectivity coefficient (STEA/Sethanol) is as high as 5.30, about 3.3 times higher than that of bare In2O3 (1.59). The sensitization mechanism of Ag on In2O3 is discussed in detail.